Progressive Muscle Relaxation: Alternatif Mengurangi Gejala pada Pasien Kemoterapi - Hamudi Prasestiyo; Allenidekania Allenidekania; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to analyze progressive muscle relaxation intervention as an alternative to reduce symptoms in patients with chemotherapy. The method used is a systematic literature review through the Science Direct, Proquest, and Scopus databases. The results of this study indicate that 6 scientific articles obtained show that progressive muscle relaxation can reduce physical symptoms such as pain and fatigue and reduce psychological symptoms such as depression, stress, anxiety, drowsiness, increase appetite, improve coping, self-efficacy, increase comfort and quality of life in chemotherapy-induced cancer patients. In conclusion, progressive muscle relaxation can reduce symptoms in cancer patients with chemotherapy physically and psychologically. Keywords: Chemotherapy, Cancer Patients, Progressive Muscle Relaxation